Domestic Homicide: A Synthesis of Systematic Review Evidence. (April 2023) - Kim, Bitna; Merlo, Alida V.
Domestic homicide (DH) is the most extreme form of domestic violence (DV). There has been a growing worldwide interest in DH offenses and the characteristics of perpetrators and victims, and it is evidenced in part by the increase in the number of primary research studies in this area. The findings of a large number of the available primary literature have already been summarized into several systematic reviews. The principal purposes of this study were to identify what types and aspects of DH have been reviewed systematically (research trends), to synthesize findings from recent systematic reviews of the theoretical and empirical literature on the different types of DH (main findings), and to consider what existing reviews can tell us about the implications for policy and practice as well as future primary research (implications). The current study utilized a systematic review approach to locate systematic reviews of studies on DH. The final sample included 25 systematic review articles published from 2010 to 2020, including 12 on intimate partner homicide, eight on child homicide, and five on familicide. The main research questions varied across systematic reviews, but they included risk factors, statistics on incidence and prevalence, theories, risk assessment tools, punishment and disposition, and prevention strategies. Building on the synthesis findings, the current study concludes with suggestions for future systematic review research and implications for practice and policy efforts.